Deposit interest rates, asset risk and bank failure in Croatia - Kraft, Evan; Galac, Tomislav (Journal of Financial Stability, 2007)
Financial deregulation, while beneficial in the long-term, seems to be linked to instability. Intense competition for deposits appears to be an ingredient in instability. We examine the aftermath of deregulation in Croatia, which included rapid growth of both deposits and deposit interest rates, followed by numerous bank failures. Using panel regression techniques, we find evidence of “market-stealing” via high deposit interest rates. We connect high deposit interest rates to bank failure using logit models. High deposit interest rates were a reliable signal of risk-taking. When supervisory capabilities and powers are weak, deposit interest rate regulation may be worth considering.